A Four-Tier Diagnostic Test to Assess Pre-service Elementary Teachersâ on Electricity Magnetism - Hermita, Neni; Suhandi, Andi; Syaodih, Ernawulan; Samsudin, Achmad (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This article reports on the calculation procedure which is to recover and to device a four-tier test diagnostic instrument, which has not been defined in the literature. It is an enhanced arrangement of the two-tier test substances. As in two-tier tests, its answer and reason tiers extent pre-service elementary teachersâ contented knowledge and clarifying knowledge, separately. The two added tiers quantity the level of confidence of pre-service elementary teacher in the accurateness of their selected choices for the answer and reason tiers separately. The four-tier diagnostic test was focussed on electricity magnetism concept. It was measured to 40 pre-service elementary teachers later. They were correctly trained on the preceding topics. The substantial corporate of the respondents was established to have an unfortunate kind and misconceptions of the subjects tested. We have already described that the test able to investigate and categorize students into student conception of electricity magnetism concepts. Research result with four tier tests showed scientific conception 5%, which was likely to have misconceptions 44.89%, and the students were lack of knowledge the concept of 46.52%, and had an error amounted to 3.59%. The pre-service elementary teachers inclined to be unwell aware among what they diagnosed and what they do not diagnosed. Kindsof question tested was connected by enhanced percentage of pre-service teacher substantial accurate responses, established buoyancy and enhanced perception calculation. 23 truthful misconceptions were predictable. It might be determined that a Four-Tier Diagnostic Test which has previously been established be able to assess pre-service elementary teachersâ conception on electricity magnetism.